2019
DOI: 10.3390/plants8060169
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Communities Associated with Peacock and Cercospora Leaf Spots in Olive

Abstract: Venturia oleaginea and Pseudocercospora cladosporioides are two of the most important olive fungal pathogens causing leaf spots: peacock spot, and cercosporiosis, respectively. In the present study, fungal communities associated with the presence of these pathogens were investigated. Overall, 300 symptomatic and asymptomatic trees from different cultivars were sampled from Alentejo, Portugal. A total of 788 fungal isolates were obtained and classified into 21 OTUs; Ascomycota was clearly the predominant phylum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Several studies have reported similar results [3,63]. Fungal communities of olive cultivars showed significant varied fungal richness and composition associated with the presence of olive pathogens causing leaf spots [64]. Two peach cultivars have different capacities for disease resistance, and with different bacterial communities, increased proportions of antagonistic bacteria might contribute to the natural defense of the resistant cultivar [65].…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have reported similar results [3,63]. Fungal communities of olive cultivars showed significant varied fungal richness and composition associated with the presence of olive pathogens causing leaf spots [64]. Two peach cultivars have different capacities for disease resistance, and with different bacterial communities, increased proportions of antagonistic bacteria might contribute to the natural defense of the resistant cultivar [65].…”
Section: Discussionmentioning
confidence: 89%
“…With reference to the geographic origin, not surprisingly the great majority of these records come from the Mediterranean region, where olive growing is absolutely dominant in statistical terms with approximately 10.2 million hectares in 2018, corresponding to more than 97% of the overall surface destined to this crop in the world [ 44 ]. In addition to geographic and climatic conditions, differences in the species assortment are related to several factors, such as plant organ ( Table 1 ), phenological stage [ 34 ], cultivar [ 22 , 27 , 29 , 32 , 35 ], season and cardinal orientation of samplings [ 23 , 24 , 26 , 29 ], isolation procedure, and substrate employed [ 33 ].…”
Section: Occurrence and Ecological Implications Of Endophytic Fungmentioning
confidence: 99%
“…Based on previous citations as fungal antagonists and producers of bioactive secondary metabolites, other species included in Table 1 may have a role in defensive mutualism [ 12 , 15 , 16 , 19 ], such as Chaetomium globosum [ 85 ], and species of Paraconiothyrium [ 86 ], Alternaria [ 87 ], and Epicoccum [ 88 ]. Strains of the two latter genera were found at a significantly higher rate in asymptomatic leaves in a survey carried out in Portugal considering the key leaf pathogens of olive tree Venturia oleaginea and Pseudocercospora cladosporioides , which may be indicative of an antagonistic role against the above disease agents [ 32 ]. Similar considerations have been advanced for Chromelosporium carneum and other taxa in the Pezizales (e.g., Heydenia and Pyronema ); in fact, these fungi were more frequent in plants which did not show symptoms of the olive knot disease [ 27 ].…”
Section: Occurrence and Ecological Implications Of Endophytic Fungmentioning
confidence: 99%
“…The endophytes are defined as microorganisms that colonize healthy internal plant tissues without causing any apparent disease symptoms [32] and may also confer tolerance to environmental stresses and pathogens [33]. The endophytic community in a single plant is usually composed of numerous species of fungi [34], and their number and species composition are influenced by the environment, plant physiology, anthropogenic factors, and pathogen infections [30,[35][36][37]. Therefore, for all the reasons listed before, the knowledge of endophytic communities in grapevine has an important role for future studies on disease management.…”
Section: Introductionmentioning
confidence: 99%